Use of anterior maxillary distraction osteogenesis in two cleft lip and palate patients - Srivastava, Dhirendra (Natl J Maxillofac Surg, 2015)
Distraction osteogenesis (DO) has become a mainstream surgical technique for patients with jaw deformities. The aim of this study was to report the effect of DO done by a hyrax screw incorporated in an acrylic plate in the treatment of two maxillary deficient cases with cleft lip and palate. Two patients, a 24-year-old female and a 29-year-old male who suffered from maxillary deficiency and cleft lip and palate, were treated by DO. After making vertical cuts between the premolars on both sides and horizontal cuts similar to Le Fort 1, a hyrax screw was mounted on an acrylic plate for the slow anteroposterior expansion of maxillary arch. The expansion was achieved by turning the hyrax screw 0.8 mm per day after the latency period. Treatment was discontinued after achieving satisfactory over jet and occlusion. This study showed that anterior maxillary distraction is a reliable technique for correction of midfacial deformity arising out of cleft lip and palate. Incidences of complications are negligible compared to total maxillary distraction.